Dear Dad: I’m still trying to make sense of some history - Anderson, Christian (ACME)

(untitled) (Centre for Social Spatial & Economic Justice at the University of British Columbia, 2024)
This letter remembers the writer's father, considering the disquieted contexts of his life and early death. These contexts connect to histories and conditions far more extensive than any individual life, and suggest difficult questions about inheritance, relationality, aftermath, settler being, and more, with which the writer continues to grapple.